2012
DOI: 10.1016/j.cmet.2012.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Fumarate Is Cardioprotective via Activation of the Nrf2 Antioxidant Pathway

Abstract: SummaryThe citric acid cycle (CAC) metabolite fumarate has been proposed to be cardioprotective; however, its mechanisms of action remain to be determined. To augment cardiac fumarate levels and to assess fumarate's cardioprotective properties, we generated fumarate hydratase (Fh1) cardiac knockout (KO) mice. These fumarate-replete hearts were robustly protected from ischemia-reperfusion injury (I/R). To compensate for the loss of Fh1 activity, KO hearts maintain ATP levels in part by channeling amino acids in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
188
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(199 citation statements)
references
References 59 publications
11
188
0
Order By: Relevance
“…Other experimental studies also showed cellular accumulation of succinate during hypoxia in rabbits7 and on ischemia in the isolated, perfused mouse heart 8. In the current study, we report that cardiac‐specific release of succinate is a feature of human IRI in patients undergoing emergency PPCI for STEMI, most likely reflecting succinate accumulation during ischemia and subsequent release from ischemic myocardial tissue following reperfusion.…”
Section: Discussionsupporting
confidence: 68%
“…Other experimental studies also showed cellular accumulation of succinate during hypoxia in rabbits7 and on ischemia in the isolated, perfused mouse heart 8. In the current study, we report that cardiac‐specific release of succinate is a feature of human IRI in patients undergoing emergency PPCI for STEMI, most likely reflecting succinate accumulation during ischemia and subsequent release from ischemic myocardial tissue following reperfusion.…”
Section: Discussionsupporting
confidence: 68%
“…The Krebs, or citric acid, cycle occurs at the junction between glycolysis and oxidative phosphorylation (8) and is a key component of aerobic metabolism by providing reducing equivalents for the electron transport chain. Interestingly, succinate has been known for many years to increase in tissues during hypoxia (9)(10)(11) and may act as a surrogate marker for reduced oxygenation. Accordingly, Sucnr1 may be activated in times of hypoxic stress such as ischemic injury in liver (12) or retina (13) or during cardiomyocyte crisis (14).…”
mentioning
confidence: 99%
“…Fumarate is an intermediate formed by the oxidation of succinate. Fumarate has a cytoprotective effect via activation of Nrf2 with the upregulation of protective antioxidant response element genes, by modification of the negative regulator KEAP 1 (Adam et al., 2011; Ashrafian et al., 2012). Temporal measurement of retinal fumarate showed that the content was significantly increased by IF and 3HB‐r compared with that in the AL group (Figure 4a).…”
Section: Resultsmentioning
confidence: 99%